The role of work volition and organizational commitment in the relationship between total rewards and employee retention - Alamzeb Aamir, 1983- , author 605556; Abu Bakar Abdul Hamid, supervisor 621919; Mohd. Norfian Alifiah, supervisor 347881; Fakulti Pengurusan 538641 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D (Pengurusan))